2012
DOI: 10.1029/2011wr011582
|View full text |Cite
|
Sign up to set email alerts
|

Physical controls and predictability of stream hyporheic flow evaluated with a multiscale model

Abstract: [1] Improved predictions of hyporheic exchange based on easily measured physical variables are needed to improve assessment of solute transport and reaction processes in watersheds. Here we compare physically based model predictions for an Indiana stream with stream tracer results interpreted using the Transient Storage Model (TSM). We parameterized the physically based, Multiscale Model (MSM) of stream-groundwater interactions with measured stream planform and discharge, stream velocity, streambed hydraulic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
102
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 88 publications
(144 reference statements)
3
102
0
Order By: Relevance
“…Since rivers have fractal topography and interactions between river flow and boundary topography drive hyporheic exchange [Harvey and Bencala, 1993;Stonedahl et al, 2010;Tonina and Buffington, 2011;Kiel and Cardenas, 2014;Gomez-Velez and Harvey, 2014], the ubiquitous fractal properties of rivers should produce fractal patterns in hyporheic flow paths and fractal scaling in the associated residence time distributions [Worman et al, 2007;Stonedahl et al, 2012]. Other mechanisms that can produce broad travel time distributions include subsurface heterogeneity and nested flow paths in homogeneous systems [Kirchner et al, 2001;Scher et al, 2002;Cardenas, 2007].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since rivers have fractal topography and interactions between river flow and boundary topography drive hyporheic exchange [Harvey and Bencala, 1993;Stonedahl et al, 2010;Tonina and Buffington, 2011;Kiel and Cardenas, 2014;Gomez-Velez and Harvey, 2014], the ubiquitous fractal properties of rivers should produce fractal patterns in hyporheic flow paths and fractal scaling in the associated residence time distributions [Worman et al, 2007;Stonedahl et al, 2012]. Other mechanisms that can produce broad travel time distributions include subsurface heterogeneity and nested flow paths in homogeneous systems [Kirchner et al, 2001;Scher et al, 2002;Cardenas, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…The exchange of water between surface and subsurface flows, generally termed hyporheic exchange, plays a critical role in structuring fluvial ecosystems [Boulton et al, 1998;Aubeneau et al, 2015]. Several studies have shown that fractal topography can produce scaling in hyporheic residence time distributions [Stonedahl et al, 2012[Stonedahl et al, , 2013Gomez-Velez and Harvey, 2014]. Worman et al [2006Worman et al [ , 2007 used numerical experiments to demonstrate the link between fractal topography and water storage times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies (Stonedahl et al, 2010;Stonedahl et al, 2012;Marion et al, 2008;Salehin et al, 2004, Elliot andBrooks, 1997b;Sawyer, 2009;Buffington & Tonina, 2009) require hydraulic conductivity values. Our research group found methods to measure the K-value that were expensive (Humboldt 2016B;Gilson;2016, Eijkelkamp, 2016 and methods, which we could not reproduce with precision or accuracy (Conners, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the 25 next sections we discuss how temporal and spatial variations in groundwater and river levels influence the extent of the HZ and HEF. Within the context of groundwater dynamics, we accept that HEF takes place in both losing and gaining stream conditions (Harvey and Bencala, 1993;Harvey et al, 2003;Stonedahl et al, 2012;Fox et al, 2014) although the way it occurs is a function of regional groundwater and catchment characteristics interacting with smaller-scale reach properties (Larkin and Sharp, 1992;Wondzell and Gooseff, 2013).…”
mentioning
confidence: 99%